2018
DOI: 10.22271/ortho.2018.v4.i1d.38
|View full text |Cite
|
Sign up to set email alerts
|

Study of clinical and functional outcome of total hip replacement in avascular necrosis of femoral head

Abstract: Avascular necrosis (AVN) of the femoral head is one of the common causes of painful hip in a young adult. Since young age is associated with high functional demand AVN may have a devastating effect on the quality of life. The natural course of this disease is one of relentless progression with eventual collapse of the femoral head followed by secondary osteoarthritic changes in the hip. The management depends upon many factors including severity and location of necrotic lesion, patient factors and probability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
(19 reference statements)
1
5
0
Order By: Relevance
“…Results were similar to the study done by Kakaria et al 9 where all 20 patients had Good to Excellent results. Similarly, in the study done by Reddy et al, 6 all 30 patients had results Good to Excellent.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Results were similar to the study done by Kakaria et al 9 where all 20 patients had Good to Excellent results. Similarly, in the study done by Reddy et al, 6 all 30 patients had results Good to Excellent.…”
Section: Discussionsupporting
confidence: 57%
“…In our study, history of steroid intake was present in 17.5% patients. In the study conducted by Reddy et al, 6 6.67% patients had history of steroid use. Wu et al 12 in his study concluded fat hypertrophy, intravascular coagulation & fat emboli as important risk factors of steroid-induced ischemic bone necrosis which may develop during initial 1 year of steroid intake.…”
Section: Discussionmentioning
confidence: 90%
“…The grading of outcome in our study was in line with the studies. 12,[18][19][20] In our study there were no dislocations with the posterolateral approach and posterior soft tissue repair. Kim et al reported three dislocations in his study which were attributed to the use of 22 mm head and habitual squatting on floor.…”
Section: Discussionmentioning
confidence: 97%
“…This is comparable to other studies. 11,12 Our study group comprised of both posttraumatic as well as non-traumatic AVN of femoral head.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation